2020
DOI: 10.25259/apos_125_2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality and reliability of websites about orthognathic surgery using Google Trends™ application

Abstract: Objectives: Orthognathic surgery is the only treatment option for some cases in orthodontics. Two main goals were aimed in this study. The first goal was to determine the top three keywords that Google searchers look for “orthognathic surgery” using the Google Trends™ application. The second was to assess the quality and reliability of the webpages yielded by searching those four keywords on Google. Materials and Methods: Google Trends was searched using the keyword “Orthognathic Surgery.” Then, Google was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…13 It has been concluded from the studies that 75% of people who receive health-related information did not control the source of this information. 14 As an illustration, a 2017 survey in our nation found that 66.3 percent of internet users in Türkiye utilized the internet to get information on their health. 15 Considering these results, the accuracy and control of the information on the internet is extremely important.…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been concluded from the studies that 75% of people who receive health-related information did not control the source of this information. 14 As an illustration, a 2017 survey in our nation found that 66.3 percent of internet users in Türkiye utilized the internet to get information on their health. 15 Considering these results, the accuracy and control of the information on the internet is extremely important.…”
Section: Discussionmentioning
confidence: 99%
“…It is a known fact individuals get information from the internet before consulting a physician when they have a health problem 20 . A study showed that 8 of 10 people use the internet to reach health information 21 . According to Turkish Statistical Institute 2019 data, searching health information (69,8%) is among the most common purposes of using the internet in Turkey 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 75% of individuals getting health information from the internet did not check the source of this information. In this respect, it is substantial to check the reliability and correctness of information on the internet 21,25 . The study is among the first studies that have evaluated patient information texts in Turkish about sedation in pediatric dentistry, in terms of both readability and content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Çalışmamızda da yalnız Türkçe metinlere bakıldığı için Ateşman okunabilirlik formülü kullanılmıştır.Turkiye'de en çok kullanılan arama motoru Google'dır.16 Çalısmamızda arama motoru olarak sadece Google kullanılmısţır. Yapılan araştırmalarda sağlıkla ilgili bilgi alan kişilerin % 75'inin bu bilginin kaynağını kontrol etmediği sonucuna ulaşılmıştır 17. 2017 yılında ülkemizde yapılan bir çalışmada, Türkiye'deki internet kullanıcılarının % 66.3' ü, sağlıklarıyla ilgili bilgilere erişmek için interneti kullandığı görülmüştür 18.…”
unclassified